EXCLUSION, DISCRIMINATION AND DISABILITY: DISCOURSE ABOUT DISABILITY IN THE PLENARY SESSION OF THE COSTA RICAN LEGISLATIVE ASSEMBLY - Vergara Heidke, Adrián (2019)
The objective of this article is to analyze the discourse of disability that is expressed in the Plenary Session of the Costa Rican Legislative Assembly, in order to identify those components that may be exclusionary and discriminatory for people with disabilities. Theoretical foundations and methodological categories of critical discourse analysis have been applied. The results show discriminatory and disparaging constructions towards people with disabilities by Legislative Assembly members.